Vaccination for hepatitis C - characterising the host immune response and its implications for a successful therapeutic vaccine - Halliday, J; John Halliday (2013)
This thesis explores the first-ever administration of a prime/boost combination of adenovirus and MVA vector based vaccines that target hepatitis C virus (HCV) infection to humans. Therapeutic application of these vaccines in patients with chronic HCV infection is first detailed, together with an interrogation of the immune responses generated. Vaccination safely induces novel T cells that target HCV immunogen in 5/11 vaccinated patients. However, assessment of circulating virus reveals significant sequence differences between autologous virus and the corresponding peptide in the vaccine immunogen. Further analysis shows that T cells induced by vaccination are poorly cross-reactive against autologous virus epitopes. Compared with vaccination in healthy individuals, T cell responses are reduced in their frequency, magnitude and breadth in HCV infected patients who receive vaccination, either alone or in combination with standard HCV treatment (pegylated interferon-α (PEG-IFN)/ribavirin). To help explain the reason for attenuated vaccine responses in HCV infected patients, I next explored baseline and PEG-IFN/ribavirin induced differences in circulating lymphocyte subpopulations. At baseline, high proportions of regulatory T cells and NKbright cells suggest both adaptive and innate immunity is altered by chronic HCV infection. During the first 28 days of therapy, complex changes in the activation, differentiation status and cytokine profiles of circulating lymphocytes are observed over time. Intriguingly, PEG-IFN causes a transient but significant decrease in circulating lymphocytes that express CXCR3, a liver homing chemokine receptor. Finally, the hypothesis that HCV therapy induces CXCR3 mediated hepatic sequestration of lymphocytes was explored. In-vivo, PEG-IFN caused a transient but profound elevation of plasma IP-10 (a CXCR3-binding chemokine) and this correlated with declines in circulating CXCR3+ CD8+ T cells in HCV infected patients. Although in-vitro experiments show IFN-α drives hepatocytes to produce IP-10, it also causes lymphocytes to down-regulate CXCR3. Unfortunately, exogenous IFN-α does not objectively demonstrate hepatic enrichment of CXCR3+ lymphocytes in a murine model.